P3_3 Stardew Planet - Sampson, Branden; Whelan, Evan; Wedge, Symran; Knight, Daniel (Physics Special Topics, 2021)
In this paper we discuss the orbital and stellar requirements for a planet with Earth like conditions but with an an orbit of only 112 days as demonstrated in the game Stardew Valley. We determine that an orbit of 0.388 Au, with a star of mass 0.623 Solar Masses, luminosity of 0.151 Solar Luminosity, radius 0.623 Solar Radii and a surface temperature of 4580K is the most likely configuration for these conditions.